Who needs more than standard care? Treatment moderators in a randomized clinical trial comparing addiction treatment alone to addiction treatment plus anxiety disorder treatment for comorbid anxiety and substance use disorders. (August 2018) - Wolitzky-Taylor, Kate; Niles, Andrea N.; Ries, Richard; Krull, Jennifer L.; Rawson, Richard; Roy-Byrne, Peter; Craske, Michelle
Abstract: Introduction: Understanding for whom treatments exert their greatest effects is crucial for prescriptive recommendations that can improve overall treatment efficacy. Anxiety and substance use disorder comorbidity is prevalent and a significant public health concern. Little is known about who should receive specialized, integrated treatments to address both problems. This study aimed to examine baseline patient characteristics that predict differential outcome between typical treatment for substance use disorders (UC) compared to that treatment combined with cognitive behavioral therapy for anxiety disorders (UC + CALM ARC). Methods: We examined several putative treatment moderators in a dataset of community-based participants (N = 75) from a randomized clinical trial at an outpatient community substance use disorder (SUD) specialty clinic. Participants who met criteria for any anxiety disorder and any SUD were randomized to UC (the Intensive Outpatient Program at the clinic) or UC + CALM ARC. Outcome measures included anxiety symptoms, drug use, and alcohol use, and were assessed at pre-treatment, post-treatment, and a 6-month follow-up assessment. Results: Older age and female gender were associated with greater improvement on anxiety outcomes in UC + CALM ARC compared to UC. The presence of an alcohol use disorder was associated with greater improvement in alcohol use in UC + CALM ARC compared to UC. Higher opiate-related withdrawal symptoms and the presence of more SUDs were associated with greater improvement in drug use outcomes in UC + CALM ARC compared to UC. Conclusions: Several pre-treatment characteristics are associated with a return of symptoms for those who receive only UC, whereas the addition of CALM ARC prevented the return of symptoms. Implications for future research and preliminary clinical recommendations are discussed. Highlights: CBT for anxiety plus SUD treatment outperformed SUD treatment alone for patients with certain characteristics. Females and older participants showed better anxiety improvement in the combination treatment compared to usual care. Those with alcohol (v. drug) use disorder showed better alcohol use outcome in the combination treatment than in usual care. Patients with opiate withdrawal symptoms at baseline had better long-term drug outcomes in the combination treatment.